If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -21)(x + 1) = 0 Reorder the terms: (-21 + 3x)(x + 1) = 0 Reorder the terms: (-21 + 3x)(1 + x) = 0 Multiply (-21 + 3x) * (1 + x) (-21(1 + x) + 3x * (1 + x)) = 0 ((1 * -21 + x * -21) + 3x * (1 + x)) = 0 ((-21 + -21x) + 3x * (1 + x)) = 0 (-21 + -21x + (1 * 3x + x * 3x)) = 0 (-21 + -21x + (3x + 3x2)) = 0 Combine like terms: -21x + 3x = -18x (-21 + -18x + 3x2) = 0 Solving -21 + -18x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-7 + -6x + x2) = 0 Factor a trinomial. 3((-1 + -1x)(7 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solution
x = {-1, 7}
| -60z^5+55z^4+25z^3=0 | | 4x-25=3x+18 | | -20=-2(v+3) | | (3x-3)(x+7)=0 | | 60z^5+55z^4+25z^3=0 | | p+0.13=53.11 | | 16-(2.1+4.5)0.2= | | -6(v-6)=78 | | u=18v | | 3n-p=6m | | t^2+t-20=0 | | p-0.13=53.11 | | 6*6=c | | 5d+2d+4d+1d=72 | | 20y^2+72y-32=0 | | 40=4(x+7) | | h/7=31 | | y=2x^2+8x+16 | | h/7=7 | | -4(1+2x)=44 | | 8m^2+14m+3=0 | | -36=-3-3(x+5) | | (6-5t)2= | | 6x+24=-2x | | 8.4o-6.8=-4.2+6.3o | | k/5=3 | | 50=6(k+8)-5k | | (x-7)-(6x+6)= | | 4x+3y=-40 | | 5x^2+3x-14=0 | | 4s^2+33s+54=0 | | 50=6(k+8)-5 |